2007
DOI: 10.1111/j.1551-2916.2007.01899.x
|View full text |Cite
|
Sign up to set email alerts
|

Doping Effects of Ta on Conductivity and Microwave Dielectric Loss of MgTiO3 Ceramics

Abstract: Two kinds of solid solution systems of Ta‐doped MgTiO3 were identified by X‐ray diffraction, which can be represented by the formulae MgTi1−x(Mg1/3Ta2/3)xO3 (0≤x<0.5) and MgTi1−xTaxO3 (0≤x<0.05). The conductivity and microwave dielectric loss for the two solid solution systems were examined by AC impedance and microwave resonator measurements, respectively. In the system MgTi1−x(Mg1/3Ta2/3)xO3, the mechanism for the solid solution formation is the isovalent substitution of for Ti4+. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…On the other hand, high quality factor (inverse of the dielectric loss, Q = 1/tan ␦) would play a more prominent role instead, since Q × f is almost constant in the microwave region [2]. It explained the research on high-Q dielectric materials, such as the MgO-TiO 2 binary system, has brought much more attention recently [3][4][5][6]. Among these compositions, MgTiO 3 and Mg 2 TiO 4 are both recognized as good candidates for high frequency applications.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, high quality factor (inverse of the dielectric loss, Q = 1/tan ␦) would play a more prominent role instead, since Q × f is almost constant in the microwave region [2]. It explained the research on high-Q dielectric materials, such as the MgO-TiO 2 binary system, has brought much more attention recently [3][4][5][6]. Among these compositions, MgTiO 3 and Mg 2 TiO 4 are both recognized as good candidates for high frequency applications.…”
Section: Introductionmentioning
confidence: 96%
“…As a result, only the tendency of dielectric constant variation can be roughly estimated if the molecule or ion with non-cubic symmetry 2,5,35 . The quality factor change of the ionic substitution is usually attributed to the grain size 20,21,23 , porosity 11,12 , structure 24 , phase evolution 5 , internal strain 2,3638 , material conductivity 39 and so on. Huang 10 et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ohsato 37 linked the quality factor to the internal strain based on the work of Stokes 38 et al . Kuang 39 evaluated the quality factor by estimating the materials’ conductivity at microwave frequency. In all these reports, quality factor trends agree with the grain size, phase evolution, porosity, internal strain, and conductivity 5,6,10,27,3739 .…”
Section: Introductionmentioning
confidence: 99%
“…The grain boundary could act as a two-dimension defect interrupting the symmetry of the crystal, thus smaller grain size, in other words, more defects, will give rise to lower Q × f [10]. Also, the increment of electrons (Nb 5+ donor doping), resulting from high content doping: Nb 2 O 5 TiO 2 ·2Nb Ti + + 4O o x + ½O 2 + ↑2e [18,20] was another factor causing the decrease of Q × f. It has been reported that dielectric loss was proportional to conductivity, tan δ σ, so that too much substitution would lead to low Q value [18,20]. The substitution at Ti 4+ site slightly changed lattice parameters that influenced the degree of tilting of octahedral [10].…”
Section: Resultsmentioning
confidence: 99%